Palisaded Granulomatous Dermatitis Associated with Ulcerative Colitis: A Comprehensive Literature Review - Stiff, Katherine M (Cureus, 2017)
Palisaded granulomatous dermatitis is an uncommon pathologic condition potentially associated with several disorders. These include drugs, inflammatory bowel disease, multiple myelomas, rheumatoid arthritis, and systemic lupus erythematosus. An illustrative case of a man with palisaded granulomatous dermatitis who subsequently developed ulcerative colitis is described, and the characteristics of other individuals with ulcerative colitis-associated palisaded granulomatous dermatitis are reviewed. PubMed was used to search the following terms: palisaded, interstitial, granulomatous, dermatitis, ulcerative colitis, and neutrophilic. Papers were obtained and references were reviewed. Ulcerative colitis-associated palisaded granulomatous dermatitis is uncommon. Palisaded granulomatous dermatitis-associated ulcerative colitis has been reported in four individuals. The palisaded granulomatous dermatitis appeared from six years prior to diagnosis to 19 years following diagnosis of the patient’s gastrointestinal disease. In addition to individual and grouped papular lesions on the elbows, the morphology of palisaded granulomatous dermatitis can also present as indurated linear plaques overlying the metacarpophalangeal (MCP) joints and proximal fingers.